Pengaruh Kepemimpinan Kepala Desa, Kompetensi Aparat Desa Dan Partisipasi Masyarakat Terhadap Pengelolaan Dana Desa Di Kecamatan Peureulak Aceh Timur - Salsabila; Iqlima Azhar; Agustina Nurul Fajriah (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2026)
This study is motivated by the importance of village head leadership, village apparatus competence, and community participation in the management of village funds in Peureulak District, East Aceh Regency. Village fund management is a crucial aspect in realizing effective, transparent, and accountable village development; therefore, good governance as well as the involvement of both the community and village officials are required. This study aims to examine the effect of village head leadership, village apparatus competence, and community participation on village fund management. The population of this study consists of village offices in Peureulak District, with a total sample of 152 respondents selected using a saturated sampling technique. Data were collected through questionnaires measured using a Likert scale, and the data were analyzed using multiple linear regression with the assistance of SPSS software. The results of the study indicate that village head leadership has a positive but not significant effect on village fund management, while village apparatus competence has a positive and significant effect on village fund management. Community participation also has a positive and significant effect on village fund management. Simultaneously, the three variables have a significant effect on village fund management. The conclusion of this study emphasizes that village fund management will be more optimal when supported by good leadership, competent village officials, and active community participation at every stage of the management process.